Analisis SWOT di Instalasi Gawat Darurat (IGD) Rumah Sakit Fathma Medika Gresik untuk Meningkatkan Kunjungan Tahun 2016 (SWOT Analysis in the Emergency Room (ER) of Fathma Medika Hospital Gresik in Order to Increasing Visits 2016) - Nurika Amaliah; Yennike Tri Herawati; Eri Witcahyo (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Trauma Center is one of Fathma Medika Hospital’s featured services to handle the trauma patients in the hospital. Trauma Center is closely related to the ER where ER is a major gateway entry of patients with emergency conditions to prevent the risk of disability and death to respond time for 5 minutes and definitive time <2 hours. In addition, data showed that the number of patient visits in ER of Fathma Medika Hospital in period of January-December 2015 did not achieve the set targets. Therefore, the matter will be examined using SWOT approach to determine a strategy that could be recommended to improve traffic based on the analysis. The purpose of this study is to analyze the strength, weakness, opportunity, and threat in the ER. This type of research is descriptive with the number of respondents as many as 12 people during October 2016. The results showed that the strength of internal components include human resources, facilities, promotion, planning, organizing, implementing, and monitoring and evaluation while the weaknesses are and the amount of service tariff visit. External components into opportunities are the government policy, social, and economic while the threat is competitive. The conclusion of this study is IGD RS Medika Fathma Gresik get a score of internal and external 0.796 and 0.817 are in the first quadrant so that the strategies are rapid and aggressive growth. Keywords : Planning Strategy, SWOT Analysis, Emergency Room